Localization of a dipolar Bose-Einstein condensate in a bichromatic optical lattice - Muruganandam, P. [UNESP]; Kumar, R. Kishor; Adhikari, Sadhan Kumar [UNESP] (Iop Publishing Ltd, 2010)
By numerical simulation and variational analysis of the Gross-Pitaevskii equation we study the localization, with an exponential tail, of a dipolar Bose-Einstein condensate (DBEC) of Cr-52 atoms in a three-dimensional bichromatic optical lattice (OL) generated by two monochromatic OLs of incommensurate wavelengths along three orthogonal directions. For a fixed dipole-dipole interaction, a localized state of a small number of atoms (similar to 1000) could be obtained when the short-range interaction is not too attractive or not too repulsive. A phase diagram showing the region of stability of a DBEC with a short-range interaction and dipole-dipole interaction is given.